The Influence of Lifestyle and Product Quality on Consumer Purchasing Decisions at Bandung Distro Manna South Bengkulu - Jiri Tri Putra; Ermy Wijaya; Yesi Indian Ariska (UNIVED Press, 2024)
The purpose of this study was to determine the influence of Lifestyle and product quality on consumer purchasing decisions in Bandung Distro Manna Bengkulu Selatan. The sample in this study were 65 consumers who shop at Bandung Distro Manna Bengkulu Selatan. The sampling technique is accidental sampling technique. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The results of the Lifestyle analysis have a significant effect on consumer purchasing decisions at Bandung Distro Manna Bengkulu Selatan, this is evidenced by the results of the t test showing the tcount value is greater than ttable (6.256 > 1.669) and a significant value of 0.000 <0.05 means H_0 is rejected and H_a is accepted. Product quality has a significant effect on consumer purchasing decisions at Bandung Distro Manna Bengkulu Selatan, this is evidenced by the results of the t test showing the tcount value is greater than ttable (4.477 > 1.669) with a significant value of 0.000 <0.05 meaning H_0 is rejected and H_a is accepted. Lifestyle (X_1) and product quality (X_2) together have a significant effect on consumer purchasing decisions (Y) in the Bandung Distro Manna Bengkulu Selatan, this is evidenced by the F test showing the value of Fcount > Ftable (146.677 > 3.15) with a significant value of 0.000. The results of multiple regression have the equation Y = 7.005 + 0.512 (X_1) + 0.295 (X_2) + e, because the direction of the regression is positive, it means that if lifestyle and product quality increase, purchasing decisions at Bandung Distro Manna Bengkulu Selatan will also increase. Lifestyle is more influential than product quality on purchasing decisions because the lifestyle regression value of 0.512 is greater than the product quality regression value.